Transnational American memories - Hebel, Udo J. (Media and cultural memory, 2009)
The volume extends scholary explorations of U.S. American cultures of memory, commemorative identity construction, and the politics of remembrance into the topical field of transnational and comparative American studies. The interdisciplinary range of issues and materials engaged includes literary texts, personal accounts, and cultural performances from colonial times through the immediate present, the significance of war monuments and ethnic memorials in Europe, Asia, and the U.S., films about 9/11, public sculptures and the fine arts, American world℗þs fairs as international sites of memory.